2001
DOI: 10.1179/026708301101509025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of material swelling on surface roughness in diamond turning of single crystals

Abstract: The effect of material swelling on the surface roughness in ultraprecision diamond turning has been investigated. Experimental results from the power spectrum analysis indicate that the pro®le of the tool marks is distorted by the effect of swelling of the materials being cut. A good correlation exists between the surface roughness and the amount of swelling that has occurred in the machined layer. Radically different surface roughness pro®les were obtained when machining aluminium and copper single crystals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…This implies that the plastic deformation is not only along the feed marks but also in between the feed marks [10]. Although it has been reported that side swelling would lead to slightly wider tool marks in some cases, the effect is relatively insignificant when compared with deep swelling [11]. Deep swelling is due to the thrust cutting force along the main cutting edge of the tool as shown in Fig.…”
Section: Tool-nose Cut Surface In Spdtmentioning
confidence: 99%
“…This implies that the plastic deformation is not only along the feed marks but also in between the feed marks [10]. Although it has been reported that side swelling would lead to slightly wider tool marks in some cases, the effect is relatively insignificant when compared with deep swelling [11]. Deep swelling is due to the thrust cutting force along the main cutting edge of the tool as shown in Fig.…”
Section: Tool-nose Cut Surface In Spdtmentioning
confidence: 99%
“…The effect of material swelling in ultra-precision diamond turning has been investigated [10] and a good correlation between the surface roughness and the amount of elastic recovery has been shown. Influences of vibration [11][12][13] and crystallographic orientation [14] on surface roughness in diamond turning have also been investigated.…”
Section: Introductionmentioning
confidence: 97%
“…In UPM, surface roughness is influenced by many factors, including cutting conditions [3], material pile-up [4], material swelling and recovery [5,6], crystal orientation [7,8], material properties [9,10], relative vibration between tool and workpiece [11,12], tool vibration [13], and spindle vibration [14]. A plethora of research has been conducted on the machinability of non-ferrous materials, such as copper and aluminum, and on chip formation with shear angle in UPM [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%